Combination Lopinavir and Ritonavir Alter Exogenous and Endogenous Bile Acid Disposition in Sandwich-Cultured Rat Hepatocytes - Griffin, LaToya M. (The American Society for Pharmacology and Experimental Therapeutics, 2013)
Inhibition of the bile salt export pump (BSEP) can cause intracellular accumulation of bile acids and is a risk factor for drug-induced liver injury in humans. Antiretroviral protease inhibitors lopinavir (LPV) and ritonavir (RTV) are reported BSEP inhibitors. However, the consequences of LPV and RTV, alone and combined (LPV/r), on hepatocyte viability, bile acid transport, and endogenous bile acid disposition in rat hepatocytes have not been examined. The effect of LPV, RTV, and LPV/r on cellular viability and the disposition of [(3)H]taurocholic acid (TCA) and [(14)C]chenodeoxycholic acid (CDCA) was determined in sandwich-cultured rat hepatocytes (SCRH) and suspended rat hepatocytes. Lactate dehydrogenase and ATP assays revealed a concentration-dependent effect of LPV and RTV on cellular viability. LPV (5 µM), alone and combined with 5 µM RTV, significantly decreased [(3)H]TCA accumulation in cells + bile of SCRHs compared with control. LPV/r significantly increased [(3)H]TCA cellular accumulation (7.7 ± 0.1 pmol/mg of protein) compared with vehicle and 5 µM LPV alone (5.1 ± 0.7 and 5.0 ± 0.5 pmol/mg of protein). The [(3)H]TCA biliary clearance was reduced significantly by LPV and RTV and further reduced by LPV/r. LPV and RTV did not affect the initial uptake rates of [(3)H]TCA or [(14)C]CDCA in suspended rat hepatocytes. LPV (50 µM), RTV (5 µM), and LPV/r (5 and 50 µM/5 µM) significantly decreased the accumulation of total measured endogenous bile acids (TCA, glycocholic acid, taurochenodeoxycholic acid, glycochenodeoxycholic acid, and α/β-tauromuricholic acid) in SCRH. Quantification of endogenous bile acids in SCRH may reveal important adaptive responses associated with exposure to known BSEP inhibitors.